Waiting time-based staff capacity and shift planning at blood collection sites. Issue 2 (4th May 2018) - van Brummelen, S. P. J.; van Dijk, N. M.; van den Hurk, K.; de Kort, W. L.
ABSTRACT: Sanquin, the organization responsible for blood collection in the Netherlands, aims to be donor-friendly. An important part of the perception of donor-friendliness is the experience of waiting times. At the same time, Sanquin needs to control the costs for blood collection. A significant step to shorten waiting times is to align walk-in arrivals, and staff capacity and shifts. We suggest a two-step procedure. First, we investigate two methods from queuing theory to compute the minimum number of staff members required for every half hour. Next, these minimum numbers of staff members will be used to determine optimal lengths and starting times of shifts with an Integer Linear Program. Finally, the practical implications of the method are shown with numerical results. These results show that the presented approach can bring significant savings while at the same time guaranteeing a waiting time-based service level for blood donors.